1983
DOI: 10.2307/1130049
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Structure of Play Objects on the Pretend Play of Low-Income Preschool Children

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. Society forResearch in Child Development, Wiley are collaborating with JSTOR to digitize, preserve and extend access to Child Development This content downloaded from 198.91.37… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(24 citation statements)
references
References 13 publications
3
15
0
Order By: Relevance
“…A distinguishing contextual component of Pretend play was found to be the use of toys or props, which was the greatest discriminator between play subtypes overall. This finding supports previous studies demonstrating that the use of toys or props facilitates Pretend play (Olsweski & Fuson, 1982;McLoyd, 1983;Rubin et al, 1985;Pellegrini & Perlmutter, 1989).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A distinguishing contextual component of Pretend play was found to be the use of toys or props, which was the greatest discriminator between play subtypes overall. This finding supports previous studies demonstrating that the use of toys or props facilitates Pretend play (Olsweski & Fuson, 1982;McLoyd, 1983;Rubin et al, 1985;Pellegrini & Perlmutter, 1989).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, criteria cited by adults and children for each subtype will be compared to determine whether there is consistency across age groups. In accordance with previous literature it is hypothesized that there will be a higher proportion of non-literality (Fein, 1981;Rubin et al, 1983;Howes et al, 1992;Lillard, 1993;Pellegrini & Smith, 1998a), communication/intimacy (Rubin et al, 1985;Howes et al, 1992;Packer, 1994; and physical (use of toys/props) (Olsewski & Fuson, 1982;McLoyd, 1983;Rubin et al, 1983;Pellegrini & Perlmutter, 1989) criteria cited for Pretend play excerpts.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Additionally, research suggests that play behavior is influenced by the play contexts and play materials (Henniger, 1985;Larson et al, 1990;McLoyd, 1983;Pellegrini & Galda, 1982;Pellegrini et al, 1984;Shim et al, 2001) and play partners (Doyle et al, 1980;Matthews, 1978;Hadley & Rice, 1991;Hartup, 1978;Howes, 1983;Howes et al, 1994;Rice, 1993). Rubin's (2001) play observation scale included social play behavior categories (solitary, parallel, and cooperative play behaviors) and cognitive play behaviors categories (functional play, constructive play, pretend/dramatic play, and games with rules).…”
Section: Introductionmentioning
confidence: 99%
“…The findings in these studies were not entirely consistent and also demonstrated deaf children's play behaviors were inferior when compared to those of their hearing peers. Additionally, research suggests that play behavior is influenced by the play contexts and play materials, (Henniger, 1985;Larson, Greenfield & Land, 1990;McLoyd, 1983;Pellegrini & Galda 1982;Pellegrini, Galda & Rubin, 1984;Shim, Herwig & Shelley, 2001) and play partners (Doyle et al, 1980;Matthews, 1978;Hadley & Rice, 1991;Hartup, 1978Hartup, , 1983Howes, 1983;Howes et al, 1994;Rice, 1993).…”
Section: Introductionmentioning
confidence: 99%